2017
DOI: 10.20473/ijosh.v6i1.2017.97-106
|View full text |Cite
|
Sign up to set email alerts
|

Postur Kerja Dengan Keluhan Musculoskeletal Disorders Pada Pekerja Manual Handlingbagian Rolling Mill

Abstract: In the production process, a lot of activities that use human power, for example in material processing, packing and transportation of production manually. It if is not done the right way, it will lead to disruption in the system of muscles, bones, tendons, and nerves called with musculoskeletal disorders. This study was conducted to determine the relationship between work posture with the incidence of musculoskeletal disorders complaint. This research is an analytic observational with cross sectional approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
9
0
20

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 4 publications
6
9
0
20
Order By: Relevance
“…Based on the results of the Nordic Body Map questionnaire, it was found that many points of complaint experienced by respondents including lower neck, left shoulder, right shoulder, back, lower waist, buttocks, right wrist, left wrist, left thigh, right thigh, left calf and right calf points. It is in accordance with Koiri who affirmed that more than 250 respondents in his study experienced health problems in the form of MSDs 11 . Importantly, a study conducted by Sangeeta and Debkumar also concluded that the upper body areas that experience many complaints among weavers of Assam Industry in Guwahati, India were neck, back, and hands 12 .…”
Section: Discussionsupporting
confidence: 90%
“…Based on the results of the Nordic Body Map questionnaire, it was found that many points of complaint experienced by respondents including lower neck, left shoulder, right shoulder, back, lower waist, buttocks, right wrist, left wrist, left thigh, right thigh, left calf and right calf points. It is in accordance with Koiri who affirmed that more than 250 respondents in his study experienced health problems in the form of MSDs 11 . Importantly, a study conducted by Sangeeta and Debkumar also concluded that the upper body areas that experience many complaints among weavers of Assam Industry in Guwahati, India were neck, back, and hands 12 .…”
Section: Discussionsupporting
confidence: 90%
“…Ergonomic risk factors with repetitive movement caused repetitive strain injury that will have an impact on the emergence of musculoskeletal complaints (Graveling, 2019). It is also in line with the study performed by Evadarianto and Dwiyanti (2017) showing that there was a very strong correlation between ergonomic risk factor and musculoskeletal complaints. Ergonomic risk factors can cause pressure or compression on tendons, nerves, bones and body organs.…”
Section: The Correlation Between Ergonomic Factor and Musculoskeletalsupporting
confidence: 91%
“…Unergonomic working posture make up the position of the body parts move away from natural positions. This posture shows strong evidence as a risk factor which can lead to musculoskeletal grievance 20 .…”
Section: Musculoskeletal Grievancementioning
confidence: 95%